2019
DOI: 10.1097/ee9.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality and cigarette smoking in a cohort of healthy fertile men

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
1
19
2
2
Order By: Relevance
“…98 Evaluating socio-demographic characteristics, in this cohort current smokers were about one out of four men, mainly reporting a mild consumption. Previous studies on fertile men 14,21,[99][100][101] found relatively higher rates of current smokers than the present study. To date, considering previous studies 14,21,[99][100][101] In the present study, alcohol consumption was reported by one out of three men, mainly as a mild intake, and was associated with a lower sperm vitality compared to the rest of the sample.…”
Section: F I G U R Econtrasting
confidence: 80%
See 1 more Smart Citation
“…98 Evaluating socio-demographic characteristics, in this cohort current smokers were about one out of four men, mainly reporting a mild consumption. Previous studies on fertile men 14,21,[99][100][101] found relatively higher rates of current smokers than the present study. To date, considering previous studies 14,21,[99][100][101] In the present study, alcohol consumption was reported by one out of three men, mainly as a mild intake, and was associated with a lower sperm vitality compared to the rest of the sample.…”
Section: F I G U R Econtrasting
confidence: 80%
“…Previous studies on fertile men 14,21,[99][100][101] found relatively higher rates of current smokers than the present study. To date, considering previous studies 14,21,[99][100][101] In the present study, alcohol consumption was reported by one out of three men, mainly as a mild intake, and was associated with a lower sperm vitality compared to the rest of the sample. Previous meta-analyses showed that alcohol intake has a detrimental effect on semen volume 105,106 and normal sperm morphology.…”
Section: F I G U R Econtrasting
confidence: 80%
“…(1) Fertility Very common habits, like smoking or alcohol intake, could influence paternal sexual functions at different levels. Studies suggest a detrimental effect of tobacco smoking mediated by reduced sexual hormones levels and exposure of spermatozoa to oxidative stress [41,42]. Heavy smokers present lower sperm concentration, total count and more pronounced teratozoospermia which entail decreased ART success rates although effects on sperm motility are found unaffected [41,43].…”
Section: ) Lifestyle Paternal Factorsmentioning
confidence: 99%
“…Studies suggest a detrimental effect of tobacco smoking mediated by reduced sexual hormones levels and exposure of spermatozoa to oxidative stress [41,42]. Heavy smokers present lower sperm concentration, total count and more pronounced teratozoospermia which entail decreased ART success rates although effects on sperm motility are found unaffected [41,43]. In addition, smoking exposes to hazardous substances like tar, nicotine, carbon monoxide, and heavy metals (e.g., cadmium and lead) with implications for semen DNA integrity leading to aneuploidies and mutations [43].…”
Section: ) Lifestyle Paternal Factorsmentioning
confidence: 99%
See 1 more Smart Citation